Subordination and binary branching. (7th December 2022) - Neeleman, Ad; Philip, Joy; Tanaka, Misako; van de Koot, Hans
Abstract: Syntactic representations are overwhelmingly asymmetric and binary branching. We develop an account of this based on the notion that subordination must be licensed through the discharge of a unique selectional requirement. The resulting theory predicts that symmetric structures, if they exist, will allow n‐ ary branching. We argue that this prediction is borne out. (i) Core properties of coordination can be explained if coordinate structures are symmetric. (ii) There is strong evidence that coordinate structures can be n ‐ary branching. This includes new evidence from the interpretation of attributive modifiers in multitermed coordinate structures. Finally, we show that a symmetric account of coordination permits a straightforward explanation of the distribution of coordinators in English.